Women and Education: Analysis of RA Kartini's Leadership in Burt Nanus' Theory - Shabrina Salsabila; Muhammad Rizkita (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
In the current era, leadership is no longer held by men only, but women also have the same rights and ability to lead. This has been proven by one of the nation's idol figures, especially for women in Indonesia itself, namely RA Kartini. RA Kartini as a leader as well as a role model for women at that time proved to the world that women were able to realize the ideals of the nation through education. She really understands the characteristics of women that can support leadership effectiveness. In this article, there are five discussions about the leadership process, leadership type, characteristics, and vision of leadership applied by RA Kartini to fight for the education rights of Indonesian women, especially in Java as seen in the leadership theory put forward by Burt Nanus. This research is a type of library research with a qualitative approach. This research data collection technique uses documentation techniques that have the aim of explaining and providing related information. The results of the study revealed that RA Kartini implemented visionary leadership in achieving her goal of fighting for the right to education for women. It is known through the analysis of Burt Nanus' leadership theory that a leader like RA Kartini is able to motivate and inspire her people to stick to the vision that is applied and has clear communication about how to achieve the desired goals.